Culinary MSME Business Development Model Post the COVID-19 Pandemic - Lela Nurlaela Wati; Tazqia Amalia (Research Synergy Foundation, 2024)
The objective of this study is to examine the influence of distribution and digital marketing on the revenue and growth of culinary micro, small, and medium enterprises (MSMEs) in Jakarta. The research used quantitative research, and the sample consisted of 251 owners of MSMEs in the culinary sector in Jakarta. The data analyses were performed using the Structural Equation Model. The food distribution channel has a favorable and substantial influence on the revenue of MSMEs in Jakarta, however it does not directly impact on the growth and advancement of MSMEs. Food distribution routes have a notable indirect impact on growth. Digital marketing does not directly impact revenue, but it does have a beneficial influence on MSME's growth and expansion. The presence of operating revenue has a favorable influence on the growth and progress of MSMEs in Jakarta. The findings of this study are valuable for advancing the field of marketing science by providing insights for stakeholders, serving as input for culinary MSMEs, and enhancing understanding of the impact of food distribution and digital marketing on MSMEs' revenue and business growth. Consequently, MSMEs can adopt more effective business strategies and improve product sales. This study thoroughly investigates the direct and indirect impact of food distribution channels and digital marketing on the revenue and growth of MSMEs. This research is unique because it employs second-order confirmatory models, which address gaps in earlier studies that mostly focused on testing direct effects.